Forms of workers’ resistance in the context of Industry 4.0 and Artificial Intelligence - Lazzareschi, Noêmia; Graglia, Marcelo Augusto Vieira; Huelsen, Patricia (Argumentum, 2021)
This article seeks to demonstrate the reactions of workers to technological and organizational changes at the national and international level. It discusses the restructuring of the production process and the delivery of services, its profound changes, and the implications for workers, governments, companies, and society. It is based on world and Brazilian literature on the Sociology of Labor that seeks to understand the attitudes and behaviors of workers at different stages of the organization of the work process, from the relationship between Taylorism/Fordism and confrontational syndicalism, Toyotism and negotiation syndicalism to the current context of industry 4.0 and artificial intelligence.